2014
DOI: 10.1155/2014/986806
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Levofloxacin in Healthy and Renal Damaged Muscovy Ducks following Intravenous and Oral Administration

Abstract: The pharmacokinetics aspects of levofloxacin were studied in healthy and experimentally renal damaged Muscovy ducks after single intravenous (IV) and oral (PO) dose of 10 mg kg−1 bwt. Following IV administration, elimination half-life (t 1/2(β)) and mean residence time (MRT) were longer in renal damaged ducks than in healthy ones. Total clearance (Cltot) in renal damaged ducks (0.20 L kg−1 h−1) was significantly lower as compared to that in healthy ones (0.41 L kg−1 h−1). Following PO administration, the peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…This variation may be attributed to the different dosage used 10 mg/kg in the current study compared to 5 mg/kg in the other studies. On the other hand, Vd ss in the current study was higher than other fluoroquinolones as levofloxacin in quails 1.25 L/Kg [34], Muscovy ducks 1.37 L/Kg [35], turkeys 1.31 L/Kg [36] and difloxacin in quails 1.54 L/Kg [37].…”
Section: Discussioncontrasting
confidence: 68%
“…This variation may be attributed to the different dosage used 10 mg/kg in the current study compared to 5 mg/kg in the other studies. On the other hand, Vd ss in the current study was higher than other fluoroquinolones as levofloxacin in quails 1.25 L/Kg [34], Muscovy ducks 1.37 L/Kg [35], turkeys 1.31 L/Kg [36] and difloxacin in quails 1.54 L/Kg [37].…”
Section: Discussioncontrasting
confidence: 68%
“…The 5 mg/kg dose used in this study was based on the dose used previously in a levofloxacin study involving broiler chicken [16]. This dose is within the range of doses previously used in other mammalian and bird species [10,15,17,18,31]; a dose associated with reduced risks of side effects. Fluoroquinolones are reported to cause tendon damage, seizures, diarrhea in humans, and blindness in cats [4], and Madsen et al [11] reported side effects, including vomiting, soft feces, and depression, after I/V administration of 15 mg/kg of levofloxacin in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Levofloxacin, a third-generation fluoroquinolone, is active against a wide range of Grampositive and Gram-negative microorganisms and has improved activity, compared to older fluoroquinolones, against streptococci and anaerobes [6,8,9]. The pharmacokinetics (PKs) of levofloxacin has already been established in several domesticated mammalian pets [7,10,11], non-pets [12][13][14], and birds [15][16][17][18]. Moreover, there are several research papers published in recent years that show increased interest in levofloxacin having potential application as an off-label drug for some pet animals (dogs).…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively lower oral bioavailabilities were reported in ducks, common pheasant, guinea fowls, Japanese quails, and chukar partridge (89.26%, 83.5%, 82.3%, 79.46%, and 47.62%, respectively; Corum et al, 2019; Dimitrova et al, 2014; Goudah & Mouneir, 2009). Meanwhile, other poultry species showed relatively low bioavailability, ranging from 69.01% to 79.89%, when orally given levofloxacin (Aboubakr, 2012; Aboubakr et al, 2014; Aboubakr & Soliman, 2014). The oral bioavailability of another fluoroquinolone (difloxacin) was reported as 84.4% and 86.2% in quails and broilers, respectively (Abo El‐Ela et al, 2014; Aboubakr & Elbadawy, 2019).…”
Section: Discussionmentioning
confidence: 99%